APA style simplified writing in psychology, education, nursing, and sociology - Beins, Bernard (Wiley-Blackwell, 2012)
"In APA Style Simplified, experienced teacher and writer Bernard C. Beins guides young scholars through the labyrinth of APA style. He highlights the major elements of APA style and shows how to generate a coherent manuscript. Beins also explores how to develop ideas, connect them to what others have written, and express them in a style that reflects a sophisticated knowledge of the subject area. In addition, he features a sample manuscript showing common deviations from APA style, and how to correct these problems. An essential resource for those working on research papers, dissertations, and manuscripts within relevant subject areas, APA Style Simplified is a compact but comprehensive guide to writing clearly and effectively"--